(untitled) (Research, Society and Development, 2023)
Soccer is one of the most popular sports in the world, characterized by motor actions of short duration and high intensity, alternating with periods of motor actions of longer duration and lower intensity. The study aims to verify the correlation between the baropodometric analysis and the incidence of injuries in soccer players. The research was carried out with a sample of 30 athletes with an average age between 18 and 35 years old, regularly hired by the club and fulfilling the training hours required by the club’s professionals. Exclusion criteria were athletes recovering from an injury in the club’s medical department and players who have musculoskeletal dysfunction or ligament injuries in the joints of the lower limbs. In soccer, short, fast and non-continuous movements impose asymmetrical loads and favor the imbalance of forces on the lower limbs. This increases the athlete’s susceptibility to injuries and makes it necessary to investigate these asymmetries in the pre-season evaluation to assist in the development of preventive programs. The characterization of the location and magnitude of plantar load parameters can help in injury prevention and rehabilitation. It was evident that the soccer players surveyed are mostly young adults, with BMI in the normal range. The baropodometric analysis of the players revealed an inversion in the mean plantar pressures in which there is a significant difference in the mean static pressure of the right foot in relation to the left foot. In addition, this research demonstrates in depth the need for further studies.